Posyandu Cadre Workshop in the Mattirowalie Village Area, West Tanete Riattang District - Hujemiati; Jumardi; Darma; Arifin, Muhammad Zainal; Fitriadi; Islawati; Murni Djabar; Riskiyani (Formosa Journal of Sustainable Research, 2024)
The aim of this service is to increase community empowerment efforts in transferring knowledge and skills from public officials to and between communities and between other communities, as well as bringing closer primary health services, especially those related to reducing maternal mortality (MMR). Infant Mortality Rate (IMR) and Child Mortality Rate (AKABA) as well as achieving the goal of a healthy city. The aim is for cadres to expand their knowledge and skills in carrying out Posyandu activities independently. The method used is to provide several hours of crash training for 3 days at 5 hours of training (45 minutes per hour). The participants were 22 Posyandu cadres in the Mattirowalie sub-district, West Tanete Riattang District. The facilities and infrastructure used are projectors, laptops, microphones, posyandu framework training modules and materials, posyandu teaching tools, sphygmomanometers, stethoscopes, scales, Dacin and Metline scales. The result of the control activity is the acquisition of knowledge after training with an average score before the test of 68, at post-test 80, so the average knowledge gain is 11 points. Cadres can also practice measuring blood pressure, weighing with Dacin, practicing the 5-table posyandu system, counseling and recording reports. The results of this charity activity are the creation of modules and publication of the results of charity activities. Facilities and infrastructure can be equipped to optimize Posyandu services. Posyandu cadres continue to increase their motivation to lead